Energy Management of Integrated Energy System in Large Ports - Huang, Wentao; Yu, Moduo; Li, Hao; Tai, Nengling (Springer Nature, 2024)
This open access book provides a detailed exploration of energy management in seaport integrated energy systems, highlighting their potential to replace conventional fuel-based energy usage and promote sustainable development of large ports. In order to achieve carbon neutrality, energy management technologies are crucial for the sustainable development of port systems that couple energies, logistics, and maritime transportation. Research on seaport integrated energy systems has attracted scholars and scientists from various disciplines, such as port electrification, logistics, microgrids, renewable energies, energy storages, and port automation. Taking a holistic approach, this book establishes a fundamental framework for the topic and discusses the electrification process, coupling mechanisms and modeling, optimal planning, low-carbon and economic operation, as well as applications of integrated energy systems in seaports. This book is intended for researchers, graduate students, and other readers interested in green seaport energy management and low-carbon operation technologies under the coupling between logistics and multi-energy systems.